A Study on The Ultrasonic Oil Extraction and Insitu Transesterification of Microalgae Biodiesel - Wiyarno, Budi; Mohd Yunus, Rosli; Mel, Maizirwan (CHEMICA: Jurnal Teknik Kimia, 2014)
The extraction and transesterification of microalgae oil are interesting topics-besides culturing and microalgae strain- in the development process of biodiesel microalgae. This is an experimental laboratory study that was run using ultrasonic homogenizer Omni Ruptor 4000, examining the effect of type of solvent, solvent concentration, alga-solvent ratio, ultrasonic power, ultrasonic time, ultrasonic pulse and mixing toward yield. Based on Box-Behnken design, a quadratic model is developed to correlate the parameter to surface area to analyze certain factors and combination of dominant factors.The result shows that power, time and pulse as the most dominant factors that influence the yield. In the extraction, the combinations of pulse-time give better result than power-pulse combination. While in the in situ transesterification, the power-time combination give better result that power-pulse combination. Even though the optimum point has not been reached yet, in general the combination of power-time is categorized as the most influential combination to increase the yield.The experimental values versus predicted values use the model equation developed by STATISTICA Software version 6.0. A line of unit slope, the line of perfect fit with points corresponding to zero error between experimental and predicted values is also shown that the coefficient of correlation (R2) is 0.97977 (for extraction) and 0.98743 (for in situ). The density of Nannochloropsis sp is 0.924 g/ml, saponication number is 114, 269 KOH/1 g oil. The percentage of FFA is 19.67% consisting of monounsaturated and polyunsaturated Octadecenoic acid (C18:1) 43.49%, Dedecanoic acid (C12) 16.30%, Hexadecanoic acid (C16:0) 12.51%, Tetradecanoic acid (C14) 11.43%, Octadecadinoic acid (C18:2) 5.85% dan Octadecanoic acid (C18:0) 5.62%.